Forrest-type IIb increases the risk of rebleeding after endoscopic treatment in patients with Dieulafoy’s lesion of the upper gastrointestinal tract - Jiayu Qiu; Yanhong Xia; Qingping Ouyang; Liping Wang; Ruiying Ding; Yang Huang; Zhenzhen Yang; Xu Shu; Xiaolin Pan; Yanxia Zhang (Annals of Medicine)
Background Dieulafoy’s lesion (DL) is a rare cause of nonvariceal upper gastrointestinal bleeding (NVUGIB) and represents a significant clinical challenge. This research aimed to identify the potential risk factors contributing to DL rebleeding after endoscopic hemostasis, including patient characteristics and laboratory and endoscopic findings such as the Forrest classification.Methods This retrospective study encompassed patients diagnosed with upper gastrointestinal DL who received standard endoscopic hemostasis between April 2007 and June 2024. Patients included in this study were categorized into the rebleeding and non-rebleeding groups. Univariate and multivariate logistic regression analyses were used to identify risk factors for DL rebleeding.Results Of the 272 patients included in this study, rebleeding occurred in 46 (16.9%). Multivariate logistic regression demonstrated that Forrest-type IIb lesions (odds ratio [OR] 3.86, 95% confidence intervals [CI] 1.16–12.83, p = 0.027) and less experienced endoscopists (OR 3.74, 95%CI 1.82–7.66, p < 0.001) were recognized as independent risk factors for rebleeding of DL in the upper gastrointestinal tract after endoscopic hemostasis. Compared with the non-rebleeding group, patients in the rebleeding group had received more transfusion units, a longer length of hospitalization, and higher rates of intensive care unit (ICU) transfer, embolization or surgery, and mortality (p < 0.005).Conclusion Forrest-type IIb lesions and less experienced endoscopists were independent risk factors for DL rebleeding in the upper gastrointestinal tract after endoscopic hemostasis. More attention should be given to DL presenting as Forrest-type IIb, as rebleeding is often closely associated with a worse clinical prognosis.